Pandangan Al-Qur'an Terhadap Peran Wanita Sebagai Ibu Dalam Mendidik Anak: The Qur'an's View Of The Role Of Women As Mothers In Raising Children - Fathiyyaturrahmah (An-Nisa’ Journal of Gender Studies, 2009)
Mother, the title commonly given to a woman entrusted by Allah SWT to conceive and give birth to children, has an active responsibility in nurturing, caring for, educating, and being a good role model for her children in order to create leaders who are capable of guiding the people. However, due to the development of the times, the role and function of mothers have been affected by women's emancipation, driven by advances in science and technology, causing modern mothers to join fathers in entering the workforce outside the home. This situation prevents mothers from focusing their attention on their children's education. Ibu, demikian panggilan yang biasa disematkan kepada seorang perempuan yang diberi kepercayaan oleh Allah SWT untuk mengandung dan melahirkan anak, mempunyai tanggung jawab secara aktif dalam mengasuh, memelihara, mendidik, dan menjadi panutan atau teladan yang baik bagi anak-anaknya agar dapat menciptakan pemimpin-pemimpin yang mampu membina umat. Akan tetapi, akibat perkembangan zaman, peran dan fungsi ibu terpengaruh akibat emansipasi wanita, didorong pula oleh kemajuan ilmupengetahuan dan teknologi membuat ibu modern turut bersama para bapak memasuki lapangan pekerjaan di luar rumah. Keadaan ini membuat ibu tidak dapat lagi memusatkan perhatiannya pada pendidikan anak.